Direct limits on the B-s(0) oscillation frequency - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2006)
We report results of a study of the Bs0 oscillation frequency using a large sample of Bs0 semileptonic decays corresponding to approximately 1fb-1 of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider in 2002-2006. The amplitude method gives a lower limit on the Bs0 oscillation frequency at 14.8ps-1 at the 95% C.L. At Δms=19ps-1, the amplitude deviates from the hypothesis A=0 (1) by 2.5 (1.6) standard deviations, corresponding to a two-sided C.L. of 1% (10%). A likelihood scan over the oscillation frequency, Δms, gives a most probable value of 19ps-1 and a range of 17<Δms<21ps-1 at the 90% C.L., assuming Gaussian uncertainties. This is the first direct two-sided bound measured by a single experiment. If Δms lies above 22ps-1, then the probability that it would produce a likelihood minimum similar to the one observed in the interval 16-22ps-1 is (5.0±0.3)%. © 2006 The American Physical Society.